Antimicrobial and antioxidant films formed by bacterial cellulose, chitosan and tea polyphenol – Shelf life extension of grass carp. (September 2022) - Zhou, Xiaoyan; Liu, Xiaoli; Wang, Qi; Lin, Guangming; Yang, Huanbin; Yu, Dawei; Cui, Steve W.; Xia, Wenshui
Abstract: To alleviate the environmental pressure caused by plastic pollution, biodegradable films made from natural polymers are gaining popularity. In the current paper, biodegradable films were successfully prepared by incorporating tea polyphenols (TP) into chitosan-bacterial cellulose (CS-BC) matrix. The effects of different concentrations (2–10% w/w) of TP on physicochemical, antioxidant and antimicrobial activities of films were systematically evaluated. The water solubility (WS), oxygen barrier property, antioxidant and antimicrobial activities enhanced as TP increased, whereas thermal stability and moisture content (MC) declined. Fourier transform infrared spectroscopy (FTIR) and scanning electron microscope (SEM) analysis indicated dense networks were formed, which was verified by enhanced physical properties. The CBT 8（8% TP）had the most significant values for elongation at break (EB), contact angle (CA), and water vapor barrier performance, and could significantly prolong the shelf life of grass carp. Overall, the findings indicated that these biodegradable films could be used for food packaging applications and reduce the environmental pollutions caused by plastics. Graphical Abstract: ga1 Highlights: CS-BC film incorporated with TP was developed to produce active food packaging. CBT composite films were prepared by the casting method and TP was well dispersed in the matrix. The addition of TP improved antioxidant and antimicrobial activity. The composite films played a considerable role on extending shelf life extension of grass carp.